Adsorption of Diclofenac Sodium and Ibuprofen by Bentonite Polyureaformaldehyde Thermodynamics and Kinetics Study - Basma Abbas Abdel Majeed; Raheem Jameel Muhseen (Iraqi Journal of Chemical and Petroleum Engineering, 2018)
An increasing number of emerging contaminants have been detected in surface waters, sediment, soil and ground water in different locations in the world, which is a new environmental challenges need an actual concern for international scientific and legislative communities.